2009
DOI: 10.1016/j.otsr.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patient's mortality and morbidity following trochanteric fracture. A hundred cases prospective study

Abstract: Level III: Prospective diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 20 publications
5
35
1
3
Order By: Relevance
“…In this study, fracture instability was found to be an independent risk factor for early death. Mnif et al, 19 in their review of 100 trochanteric fractures, also reported higher early mortality with greater instability. In their study, the fractures were not classified according to the AO/OTA classification; however, a point to note is that the relationship between fracture instability and mortality was maintained in a cohort treated by the same device, suggesting that the device or fixation type is likely to be less important.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, fracture instability was found to be an independent risk factor for early death. Mnif et al, 19 in their review of 100 trochanteric fractures, also reported higher early mortality with greater instability. In their study, the fractures were not classified according to the AO/OTA classification; however, a point to note is that the relationship between fracture instability and mortality was maintained in a cohort treated by the same device, suggesting that the device or fixation type is likely to be less important.…”
Section: Discussionmentioning
confidence: 95%
“…Osteoporotic femoral fractures are a major clinical problem with high morbidity and mortality [1,2]. Improvement of fracture risk prediction is fundamental in order to improve the patients' quality of life and to reduce the costs associated to the ageing of our society.…”
Section: Introductionmentioning
confidence: 99%
“…Wraz z szyb ko ro sną cą po pu la cją osób star szych licz ba tych zła mań sta le się zwięk sza. Sza cu je się, że w USA przed 2050 ro kiem ich licz ba wy nie sie 0,5 mln in cy den tów rocz nie, pod czas gdy na świe cie do 2025 ro ku osią gnie po ziom 6,25 mln rocz nie [3,4]. Jed ną z po wa żniej szych, mo żli wych kom pli ka cji jest brak, mi mo sta bi li za cji zła ma nia, zro stu kost ne go i w dal szej ko lej no ści po wsta nie sta wu rze ko me go [5][6][7].…”
Section: Wstępunclassified
“…With the quickly growing elderly population, the incidence of these fractures is also increasing. It is estimated that, in the USA,, the number will reach 0.5m annually before 2050 while in the world, the figure will reach 6.25m a year before 2025 [3,4]. One of the most important possible complications is bone non-union despite previous fracture stabilisation, followed by the development of a pseudarthrosis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%